Characteristics of Cancer Rehabilitation Fellowship Training Programs in the United States - Yadav, Rajesh R. (J Cancer Educ, 2018)
Cancer rehabilitation is emerging as a specialized field within Physical Medicine and Rehabilitation. The purpose of this systemic review is to summarize the various cancer rehabilitation fellowship programs in United States and the scope of training in this discipline. Currently, four institutions offer such a training program. All of the fellowship directors were contacted about characteristics of their programs. The oldest program has been in existence since 2007. All of these programs are one year in duration and have between 1 and 2 fellowship positions annually. There have been total of 29 graduates as of July 2017. With regards to cancer rehabilitation care delivery model, all 4 centers reported inpatient consult teams, and outpatient rehabilitation. Outpatient experience included electrodiagnosis, botulin toxin and ultrasound guided injections. Three of the four 4 programs also reported the presence of an acute inpatient cancer rehabilitation service. A number of clinical rotations are available at each of the four programs with considerable variation. Comprehensive educational efforts are present in all programs with varying expectations for research.